Analisis Kesiapan Guru dalam Implementasi Kurikulum Merdeka di SMP Negeri 2 Panti - Septia Sulfiani; Evrialiani Rosba; Aulia Afza (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
This research is motivated by the fact that teachers are not yet fully prepared to implement the Merdeka Curriculum in schools, as they do not fully understand the curriculum structure, Learning Outcomes (LO), Learning Objectives (LO), Learning Objective Flow (LOF), and the understanding of the Pancasila Student Profile Strengthening Project (PSPSP), which has not been fully comprehended by each teacher. Supporting facilities and infrastructure are available but are not yet complete. This study aims to analyze the readiness of teachers in implementing the Merdeka Curriculum at SMP Negeri 2 Panti, Panti District, Pasaman Regency, West Sumatra Province. This research is descriptive with a qualitative approach. This method was chosen according to the needs of this research, namely to analyze the readiness of teachers at SMP Negeri 2 Panti in implementing the Merdeka Curriculum. Data analysis was conducted using a Likert scale. Based on validity tests by teachers, the understanding of the curriculum structure is categorized as very ready with an average of 92.33%. The readiness of lesson planning has an average of 95.33% with a very ready criterion. The readiness of the learning process has an average of 89% with a very ready criterion. The readiness of teaching modules has an average of 90% with a very ready criterion. The readiness of facilities and infrastructure has an average of 92% with a very ready criterion, and the readiness of assessment has an average of 94% with a very ready criterion. Teachers' readiness in implementing the Merdeka Curriculum at SMP Negeri 2 Panti is very ready to execute the Merdeka Curriculum.